A Non Linear Optimal Control Problem Related to a Road De-icing Device: Analysis and Numerical Experiments - Bernardin, Frédéric; Lemoine, Jérôme; Münch, Arnaud (Applied mathematics & optimization, 2025)
In order to design a road de-icing device by heating, we consider in a two dimensional setting the optimal control of an advection–diffusion equation with a nonlinear boundary condition of the Stefan-Boltzmann type. The problem models the heating of a road during a winter period to keep positive its surface temperature above a given threshold. The heating device is performed through the circulation of a coolant in a porous layer of the road. We prove the well-posedeness of the nonlinear optimal control problem, subject to unilateral constraints on the control and the state, set up a gradient based algorithm then discuss some numerical results associated with real data obtained from experimental measurements. The study, initially developed in a one dimensional simpler setting in [ 1 ], aims to quantify the minimal energy to be provided to keep the road surface without frost or snow.